Carbon and Cash in Climate Assemblages: The Making of a New Global Citizenship. Issue 1 (17th June 2015) - Arora‐Jonsson, Seema; Westholm, Lisa; Temu, Beatus John; Petitt, Andrea
Abstract: Climate instruments such as REDD+ (Reducing Emissions by Deforestation and Degradation) promise a win–win proposition as villagers in Africa are paid for their efforts to conserve forests and sequester carbon. REDD+ assembles divergent interests at different scales—from bureaucrats to individual villagers. We argue that climate assemblages are shifting the space of the political by regulating practices that previously had local and national provenance. They are producing "state‐like" effects that touch deeply on citizenship. Villagers are drawn into a shifting REDD+ assemblage and subject to new identifications as entrepreneurs and responsible environmental citizens, meant to look after a new global commons. We shift the discussion to deal seriously with questions of a "global" citizenship, not in its utopian sense, but by bringing into light the dark side of global citizenship already in practice in environmental governance. Forests and peoples are in practice made global—we must conceptualize the rights of this "global" citizenship